Looking back and moving forward: The experiences of canadian parents raising an adolescent with autism spectrum disorder. (August 2018) - Ho, Hilda; Fergus, Karen; Perry, Adrienne
Highlights: Using thematic analysis, this study examined parent experiences of raising a child with autism spectrum disorder (ASD) from early childhood and into adolescence. Four themes were constructed: 1) Rippling Effect of Loss; 2) Becoming a Parent-Professional; 3) One Size Fits None; and 4) Preparing for "The Future". Interventions for adolescents with ASD need to actively involve parents as well as to grow with the changing needs of the child and family. Abstract: Background: The aim of this study was to investigate parent experiences of raising a child with autism spectrum disorder (ASD) from early childhood and into adolescence. Method: Semi-structured in-depth interviews were conducted with nine families of adolescents diagnosed with ASD with a range of cognitive ability. Thematic analysis was used to analyze the parents' narratives. Findings: Four themes were constructed to represent the parents' narratives of their caregiving journey: 1) Rippling Effect of Loss; 2) Becoming a Parent-Professional; 3) One Size Fits None; and 4) Preparing for "The Future". Parental narratives reflect the tension they experience with the school system and the frustration with dealing with services that do not grow with their child's needs. Findings also indicate that, over the years, parents develop a specialized skill set that helps them navigate the ever-changing ASD landscape. Discussion: The results of this study have several important implications, including the need for service and education providers to actively involve parents in the treatment of their child, as well as to increase appropriate services for adolescents that target both ASD and comorbid mental health challenges.